Response of Nitrogen Loading to the Chesapeake Bay to Source Reduction and Land Use Change Scenarios: A SPARROW‐Informed Analysis. (14th November 2019) - Miller, Matthew P.; Capel, Paul D.; García, Ana María; Ator, Scott W.
Abstract: In response to concerns regarding the health of streams and receiving waters, the United States Environmental Protection Agency established a total maximum daily load for nitrogen in the Chesapeake Bay watershed for which practices must be in place by 2025 resulting in an expected 25% reduction in load from 2009 levels. The response of total nitrogen (TN) loads delivered to the Bay to nine source reduction and land use change scenarios was estimated using a Spatially Referenced Regression on Watershed Attributes model. The largest predicted reduction in TN load delivered to the Bay was associated with a scenario in which the mass of TN as fertilizer applied to agricultural lands was decreased. A 25% decrease in the mass of TN applied as fertilizer resulted in a predicted reduction in TN loading to the Bay of 11.3%, which was 2.5–5 times greater than the reductions predicted by other scenarios. Eliminating fertilizer application to all agricultural land in the watershed resulted in a predicted reduction in TN load to the Bay of 45%. It was estimated that an approximate 25% reduction in TN loading to the Bay could be achieved by eliminating fertilizer applied to the 7% of subwatersheds contributing the greatest fertilizer‐sourced TN loads to the Bay. These results indicate that management strategies aimed at decreasing loading from a small number of subwatersheds may be effective for reducing TN loads to the Bay, and similar analyses are possible in other watersheds.